The reality of primary school teachers' use of educational games in teaching mathematics - Al-Najei, Afrah Essa (Journal of Educational and Psychological Sciences, 2023)
The current study aims to reveal the degree to which teachers in primary classes use educational games in teaching mathematics from the teacher's own point of view and to reveal the reality of their use of educational games by sex, qualification and experience, The survey descriptive curriculum has been followed, and identification has been used as a tool for study, and its first theme is the teacher's use of educational games in mathematics teaching. and the second for obstacles to their use, and the sample of the study consisted of 228 teachers for initial grades of Al-khobar. The results of the study indicate that the use of educational toys came largely with an average arithmetic (3.77), and the obstacles to using educational games came with a large average calculation (3.42), and the existence of differences by statistical significance at the level (0.05) depending on sex. which is in favor of females on the first axis, The second axis is in favor of males, and the existence of differences by statistical indication according to experience on the first axis in favor of higher expertise, The lack of discrepancies of the second axis depending on experience, and the absence of differences depending on the qualifying variable on the first axis, Differences by statistical indication in favour of the diploma on the second axis, which indicates that teachers with diploma have a higher chance of facing obstacles than the rest of the teachers. One of the most important recommendations is the preparation of a teachers' guide containing the majority of educational games, their rules and importance, suggesting appropriate lessons for them, and a study on the role of educational games in teaching addition and subtraction from the point of view of female primary teachers.
Keywords: elementary class teachers; educational games; mathematics